Crossability In Interspecific Hybrid Between Eucalyptus Pellita and E. Urophylla - , Mulawarman; Setyono Sastrosumarto; Mohammad Na'iem (Zuriat, 2003)
A controlled crossing experiment using a factorial mating design, involving female parents of E. pellita and male parents of E. urophyla that randomly sampled from the breeding population of both species, was conducted to assess the degree of genetic control on interspecific crossability for hybrid between E. pellita and E. urophylla. As measures of crossability, number of seeds per capsule and percentage of germinated seed were determined for each individual cross. The effect of female, male and female × male was significant on number of seed per capsule and percentage of germination. There was a slight tendency that the family produced more viable seed might produce less viable seed. Additive and dominance genetic varians were estimated as measures of the genetic control. The dominance variance had the major contribution to the genetic control of seed production and seed germination. Female source of variation has the major contribution to the additive genetic influence. Therefore, to maximize the production of viable seed, parent trees with desired traits should be selected on specific cross basis.